NUMERICAL MODELING OF THE BUCKLING RESISTANCE OF RULED HELICOIDAL SHELLS - Mathieu Giloulbe; Aleksei S Markovich; Evgeniya M Tupikova; Yulian V Zhurbin (RUDN Journal of Engineering Research, 2018)
The paper concerns the buckling analysis of thin shells of right helicoid form. The buckling analysis was performed by the means of finite element software. Shells with variable pitch number and same contour radiuses and height were compared, their straight edges fixed and the curvilinear contours free. Was used for the analysis triangular shell finite elements (No. 42). The total number of nodal unknowns was the same in each of the considered tasks and was 16 206. Numerical investigation of the stability was performed by the finite element method in the software package Lira-Sapr 2017. The number of nodes in each task was the same. The loading includes combination of gravity (dead load) and vertical equally distributed load. The buckling mode and stability factor for every case is calculated. Boundary conditions - elastic built in shells along the bottom and top generatrices. To plot the midsurface of each shell were used parametric equations in rectangular coordinates. Of particular interest is the study of natural oscillations of the shells considered. To define the frequencies and forms of free vibrations is taken into account only the own weight of the helicoidal shells.